Management of Innovative Projects through Agile Technology - Bucea-Manea-Tonis, Radu; Tonis (Bucea Manea ), Rocsana (Journal of Economic Development, Environment and People, 2014)
Because of the globalization and the evolution of internet and technologies, nowadays the innovation is associated with open collaboration conducted by a legal framework. The paper analyses the methods that allow a better management for innovative projects and focuses on agile projects within a technological network.